Modelling the spatial and temporal constrains of the GABAergic influence on neuronal excitability. - Aniello Lombardi (Public Library of Science (PLoS), 2021)
GABA (γ-amino butyric acid) is an inhibitory neurotransmitter in the adult brain that can mediate depolarizing responses during development or after neuropathological insults. Under which conditions GABAergic membrane depolarizations are sufficient to impose excitatory effects is hard to predict, as shunting inhibition and GABAergic effects on spatiotemporal filtering of excitatory inputs must be considered. To evaluate at which reversal potential a net excitatory effect was imposed by GABA (EGABAThr), we performed a detailed in-silico study using simple neuronal topologies and distinct spatiotemporal relations between GABAergic and glutamatergic inputs. These simulations revealed for GABAergic synapses located at the soma an EGABAThr close to action potential threshold (EAPThr), while with increasing dendritic distance EGABAThr shifted to positive values. The impact of GABA on AMPA-mediated inputs revealed a complex temporal and spatial dependency. EGABAThr depends on the temporal relation between GABA and AMPA inputs, with a striking negative shift in EGABAThr for AMPA inputs appearing after the GABA input. The spatial dependency between GABA and AMPA inputs revealed a complex profile, with EGABAThr being shifted to values negative to EAPThr for AMPA synapses located proximally to the GABA input, while for distally located AMPA synapses the dendritic distance had only a minor effect on EGABAThr. For tonic GABAergic conductances EGABAThr was negative to EAPThr over a wide range of gGABAtonic values. In summary, these results demonstrate that for several physiologically relevant situations EGABAThr is negative to EAPThr, suggesting that depolarizing GABAergic responses can mediate excitatory effects even if EGABA did not reach EAPThr.